Africa*n Relations : Modalities Reflected (University of Bayreuth African Studies Online, 2024)
This special issue “Africa*n Relations. Modalities Reflected” comes out of the first conference of the Cluster of Excellence Africa Multiple. Reconfiguring African Studies, which took place from 14th to 17th July 2021. Like the conference, the special issue is dedicated to the cluster’s annual theme and heuristic angle of modes of relating. In the overall research agenda of the Africa Multiple, the notion of relationality takes centerstage. With the focus on Africa not as a given but as a multiple constantly in the making, relations through which it is constituted and upated necessarily come to the fore. Our attention is drawn to processes, appearances and practices and hence to the variety of modes of coming into relation. Accordingly, next to medialities, spatialities, and temporalities, modalities is a heuristic angle in Africa Multiple meant to structure the study of relations we encounter in African lifeworlds, which can take a vast spectrum of forms, like e.g. exchange, acceptance, adaptation, convergence, dependence, hierarchization, conflict, struggle, resistance, and denial. Furthermore, modalities is fundamentally interlinked with the Africa Multiple Cluster’s key concept of reflexivity, which requires the researchers to reflect upon the relational modalities of their position and the very conditions of their knowledge production. This issue’s six contributions which approach modes of relations from a variety of perspectives and with a view on different African countries and their diasporic links, were written by scholars from a variety of disciplines, namely, sociology, geography, anthropology, religious and literary studies and philosophy. Furthermore, in line with critically reflecting upon the modalities of academic knowledge production, it also contains contributions by two artists, the French photographer Aurélien Gillier, who enters in a dialogue with the sociologist Joschka Philipps, and the Kenyan author Yvonne Ahdiambo Owuor, who critically reflects on creative forms of knowledge production on and in Africa.
Keywords: relations; modalities of relations; mixed methods; ways of knowing Africa; Reflexivity; multiplicity; Mobility; Musée Dynamique; conspiracy theory; Beziehungen; Modalitäten der Beziehungen; Wissensformen über Afrika; Reflexivität; Vielfältigkeit; Mobilität; Verschwörungstheorie